The experience of connectivity: results from a survey of Australian Internet users - Allen, Matthew (Routledge (Taylor and Francis Group), 2010)
This article presents the findings from a survey of Australian Internet users (n=1172) conducted in 2007 investigating their overall experience of connectivity at home. Experience of connectivity is defined to mean how people use the Internet to achieve general outcomes of value to them in their everyday lives, and includes both the range of outcomes and the significance of the Internet in achieving them. The survey, thus, reports on the experience of a single behaviour 'using the Internet' rather than, as common in other research, multiple specific behaviours conducted while online. The article analyses the data collected to draw conclusions that provide greater depth of understanding of connectivity understood as phenomenon in and of itself. This article contributes important information about the experiences of Australian Internet users, about which there have been only a few and relatively superficial studies. It also provides an example of new approach to surveying Internet users which can lead to more direct conclusions about the value and extent of their uses of connectivity in their lives.